Optogenetic control of gut movements reveals peristaltic wave-mediated induction of cloacal contractions and reactivation of impaired gut motility - Shikaya, Yuuki; Inaba, Masafumi; Tadokoro, Ryosuke; Utsunomiya, Shota; Takahashi, Yoshiko (Frontiers in Physiology, 2023)
Gut peristalsis, recognized as a wave-like progression along the anterior-posterior gut axis, plays a pivotal role in the transportation, digestion, and absorption of ingested materials. The embryonic gut, which has not experienced ingested materials, undergoes peristalsis offering a powerful model for studying the intrinsic mechanisms underlying the gut motility. It has previously been shown in chicken embryos that acute contractions of the cloaca (an anus-like structure) located at the posterior end of the hindgut are tightly coupled with the arrival of hindgut-derived waves. To further scrutinize the interactions between hindgut and cloaca, we here developed an optogenetic method that produced artificial waves in the hindgut. A variant form of channelrhodopsin2 (ChR2(D156C)), permitting extremely large photocurrents, was expressed in the muscle component of the hindgut of chicken embryos using Tol2-mediated gene transfer and in ovo electroporation techniques. The D156C-expressing hindgut responded efficiently to local pulses of blue light: local contractions emerge at an ectopic site in the hindgut, which were followed by peristaltic waves that reached to the endpoint of the hindgut. Markedly, the arrival of the optogenetically induced waves caused concomitant contractions of the cloaca, revealing that the hindgut-cloaca coordination is mediated by signals triggered by peristaltic waves. Moreover, a cloaca undergoing pharmacologically provoked aberrant contractions could respond to pulsed blue light irradiation. Together, the optogenetic technology developed in this study for inducing gut peristalsis paves the way to study the gut movement and also to explore therapeutic methodology for peristaltic disorders.